THE EFFECT OF ISLAMIC WORK ETHIC, COMPETENCE AND MOTIVATION ON THE PERFORMANCE OF STATE MADRASAH ALIYAH TEACHERS IN SOUTH SULAWESI - Kurniati, Kurniati; Basalamah, Salim; Halim, Arief; Syahid, Akhmad (Jurnal Diskursus Islam, 2021)
This study aims to analyze the effect of Islamic work ethic, competence and motivation on the performance of State Madrasah Aliyah teachers in South Sulawesi. This research is quantitative research with a population of 1.723 teachers in State Madrasah Aliyah, South Sulawesi. The sample of this study was taken using the Slovin formula with the provisions of 10% (error level) that consist of 95 teachers from State Madrasah Aliyah in the Regency/City in South Sulawesi Province. The sampling technique uses side probability which is a random sampling technique with the provision of an error rate of 10%, regardless of the strata that exist in the population. The data of this study were analyzed using multiple linear regression analysis techniques with three independent variables and one dependent variable by testing the classical assumption test, which are heteroscedasticity, multicollinearity, autocorrelation, and residual normality test. Based on the results of multiple linear regression analysis, it shows that the significance value is 0.001. Significance < 0.005(0.001 < 0.05), then H0 is rejected. Therefore, it can be concluded that Islamic work ethic, competence, and motivation equally affect the performance of State Madrasah Aliyah teachers in South Sulawesi.